Herd on the Street: Informational Inefficiencies in a Market with Short-Term Speculation - Froot, Kenneth A.; Scharfstein, David S.; Stein, Jeremy C. (Journal of Finance, 1992)
Standard models of informed speculation suggest that traders try to learn information that others do not have. This result implicitly relies on the assumption that speculators have long horizons, i.e, can hold the asset forever. By contrast, we show that if speculators have short horizons, they may herd on the same information, trying to learn what other informed traders also know. There can be multiple herding equilibria, and herding speculators may even choose to study information that is completely unrelated to fundamentals. These equilibria are informationally inefficient.